Modelagem de processos nucleares de alta energia em explosões solares utilizando o pacote FLUKA - Tusnski, Daneele Saraçol (2018)
The emission of -rays in solar flares is produced by interactions of primary electrons and ions accelerated to high energies with nuclei in the ambient solar atmosphere. The analysis of the -ray spectra observed during solar flares provides important diagnostics on the mechanisms of primary particle acceleration and on the structure and evolution of the ambient plasma. In this work we investigate the high energy nuclear processes that occur in solar flares using FLUKA, a package of general purpose integrated routines for Monte Carlo calculations of particle transport and interactions in matter. Our main aim is to validate FLUKA as an effective tool for the modeling of nuclear processes in the context of solar flares. In order to accomplish that, we have performed simulations of the -ray spectrum considering realistic models for the ambient solar atmosphere and beams of accelerated ions (protons, -particles and heavier nuclei) with different energy and angular distributions. From the results obtained in the simulations with FLUKA, we have built templates for the nuclear de-excitation lines emission spectrum and for the full -ray emission spectrum, which were incorporated to the program OSPEX for the fitting of spectra from observed events. Using these templates in combination with standard-functions avaiable in the programa OSPEX we have obtained statistically reasonable fittings for the -ray spectra of the July 23, 2002 and June 12, 2010 solar flares, similar to the fittings obtained with templates built from nuclear de-excitation lines emission spectra calculated with the code developed by Murphy et al. (2009). To the best of our knowledge, the fittings carried out with the FLUKA templates for the full -ray emission spectrum can be regarded as the first attempt to use a single code to implement a self-consistent treatment of the several spectral components in the energy range from ∼ 100’s keV to ∼ 100’s MeV.